Effect of Dipeptidyl Peptidase 4 Inhibition on Arterial Blood Pressure is Context Dependent. Issue 1 (January 2015) - Jackson, Edwin K.; Mi, Zaichuan; Tofovic, Stevan P.; Gillespie, Delbert G.
Abstract : Because the effects of dipeptidyl peptidase 4 (DPP4) inhibitors on blood pressure are controversial, we examined the long-term effects of sitagliptin (80 mg/kg per day) on blood pressure (radiotelemetry) in spontaneously hypertensive rats (SHR), Wistar–Kyoto rats, and Zucker Diabetic-Sprague Dawley rats (metabolic syndrome model). In SHR, chronic (3 weeks) sitagliptin significantly increased systolic, mean, and diastolic blood pressures by 10.3, 9.2, and 7.9 mm Hg, respectively, a response abolished by coadministration of BIBP3226 (2 mg/kg per day; selective Y1 -receptor antagonist). Sitagliptin also significantly increased blood pressure in SHR treated with hydralazine (vasodilator; 25 mg/kg per day) or enalapril (angiotensin-converting enzyme inhibitor; 10 mg/kg per day). In Wistar–Kyoto rats, chronic sitagliptin slightly decreased systolic, mean, and diastolic blood pressures (−1.8, −1.1, and −0.4 mm Hg, respectively). In Zucker Diabetic-Sprague Dawley rats, chronic sitagliptin decreased systolic, mean, and diastolic blood pressures by −7.7, −5.8, and −4.3 mm Hg, respectively, and did not alter the antihypertensive effects of chronic enalapril. Because DPP4 inhibitors impair the metabolism of neuropeptide Y1–36 (NPY1–36 ; Y1 -receptor agonist) and glucagon-like peptide (GLP)-1(7–36)NH2 (GLP-1 receptor agonist), we examined renovascular responses to NPY1–36 and GLP-1(7–36)NH2 in isolated perfused SHR and Zucker Diabetic-Sprague Dawley kidneys pretreated with norepinephrine (to induce basal tone). In Zucker Diabetic-Sprague Dawley kidneys, NPY1–36 and GLP-1(7–36)NH2 exerted little, if any, effect on renovascular tone. In contrast, in SHR kidneys, both NPY1–36 and GLP-1(7–36)NH2 elicited potent and efficacious vasoconstriction. In conclusion: (1) The effects of DPP4 inhibitors on blood pressure are context dependent; (2) The context-dependent effects of DPP4 inhibitors are due in part to differential renovascular responses to its most important substrates (NPY1–36 and GLP-1(7–36)NH2 ); (3) Y1 receptor antagonists may prevent the prohypertensive and possibly augment the antihypertensive effects of DPP4 inhibitors. Abstract : Supplemental Digital Content is available in the text.